5.9.52 Problems 5101 to 5200

Table 5.731: First order ode linear in derivative

#

ODE

Mathematica

Maple

13282

\[ {}3 x^{2} y^{2}-y^{3}+2 x +\left (2 x^{3} y-3 x y^{2}+1\right ) y^{\prime } = 0 \]

13283

\[ {}2 y \sin \left (x \right ) \cos \left (x \right )+y^{2} \sin \left (x \right )+\left (\sin \left (x \right )^{2}-2 y \cos \left (x \right )\right ) y^{\prime } = 0 \]

13284

\[ {}y \,{\mathrm e}^{x}+2 \,{\mathrm e}^{x}+y^{2}+\left ({\mathrm e}^{x}+2 x y\right ) y^{\prime } = 0 \]

13285

\[ {}\frac {3-y}{x^{2}}+\frac {\left (y^{2}-2 x \right ) y^{\prime }}{x y^{2}} = 0 \]

13286

\[ {}\frac {1+8 x y^{{2}/{3}}}{x^{{2}/{3}} y^{{1}/{3}}}+\frac {\left (2 x^{{4}/{3}} y^{{2}/{3}}-x^{{1}/{3}}\right ) y^{\prime }}{y^{{4}/{3}}} = 0 \]

13287

\[ {}4 x +3 y^{2}+2 x y y^{\prime } = 0 \]

13288

\[ {}y^{2}+2 x y-x^{2} y^{\prime } = 0 \]

13289

\[ {}y+x \left (x^{2}+y^{2}\right )^{2}+\left (y \left (x^{2}+y^{2}\right )^{2}-x \right ) y^{\prime } = 0 \]

13290

\[ {}4 x y+\left (x^{2}+1\right ) y^{\prime } = 0 \]

13291

\[ {}x y+2 x +y+2+\left (x^{2}+2 x \right ) y^{\prime } = 0 \]

13292

\[ {}2 r \left (s^{2}+1\right )+\left (r^{4}+1\right ) s^{\prime } = 0 \]

13293

\[ {}\csc \left (y\right )+\sec \left (x \right ) y^{\prime } = 0 \]

13294

\[ {}\tan \left (\theta \right )+2 r \theta ^{\prime } = 0 \]

13295

\[ {}\left ({\mathrm e}^{v}+1\right ) \cos \left (u \right )+{\mathrm e}^{v} \left (1+\sin \left (u \right )\right ) v^{\prime } = 0 \]

13296

\[ {}\left (x +4\right ) \left (1+y^{2}\right )+y \left (x^{2}+3 x +2\right ) y^{\prime } = 0 \]

13297

\[ {}x +y-x y^{\prime } = 0 \]

13298

\[ {}2 x y+3 y^{2}-\left (2 x y+x^{2}\right ) y^{\prime } = 0 \]

13299

\[ {}v^{3}+\left (u^{3}-u v^{2}\right ) v^{\prime } = 0 \]

13300

\[ {}x \tan \left (\frac {y}{x}\right )+y-x y^{\prime } = 0 \]

13301

\[ {}\left (2 s^{2}+2 s t +t^{2}\right ) s^{\prime }+s^{2}+2 s t -t^{2} = 0 \]

13302

\[ {}x^{3}+y^{2} \sqrt {x^{2}+y^{2}}-x y \sqrt {x^{2}+y^{2}}\, y^{\prime } = 0 \]

13303

\[ {}\sqrt {x +y}+\sqrt {x -y}+\left (\sqrt {x -y}-\sqrt {x +y}\right ) y^{\prime } = 0 \]

13304

\[ {}y+2+y \left (x +4\right ) y^{\prime } = 0 \]

13305

\[ {}8 \cos \left (y\right )^{2}+\csc \left (x \right )^{2} y^{\prime } = 0 \]

13306

\[ {}\left (3 x +8\right ) \left (4+y^{2}\right )-4 y \left (x^{2}+5 x +6\right ) y^{\prime } = 0 \]

13307

\[ {}x^{2}+3 y^{2}-2 x y y^{\prime } = 0 \]

13308

\[ {}2 x -5 y+\left (4 x -y\right ) y^{\prime } = 0 \]

13309

\[ {}3 x^{2}+9 x y+5 y^{2}-\left (6 x^{2}+4 x y\right ) y^{\prime } = 0 \]

13310

\[ {}x +2 y+\left (2 x -y\right ) y^{\prime } = 0 \]

13311

\[ {}3 x -y-\left (x +y\right ) y^{\prime } = 0 \]

13312

\[ {}x^{2}+2 y^{2}+\left (-y^{2}+4 x y\right ) y^{\prime } = 0 \]

13313

\[ {}2 x^{2}+2 x y+y^{2}+\left (2 x y+x^{2}\right ) y^{\prime } = 0 \]

13314

\[ {}y^{\prime }+\frac {3 y}{x} = 6 x^{2} \]

13315

\[ {}x^{4} y^{\prime }+2 x^{3} y = 1 \]

13316

\[ {}y^{\prime }+3 y = 3 x^{2} {\mathrm e}^{-3 x} \]

13317

\[ {}y^{\prime }+4 x y = 8 x \]

13318

\[ {}x^{\prime }+\frac {x}{t^{2}} = \frac {1}{t^{2}} \]

13319

\[ {}\left (u^{2}+1\right ) v^{\prime }+4 v u = 3 u \]

13320

\[ {}x y^{\prime }+\frac {\left (2 x +1\right ) y}{1+x} = x -1 \]

13321

\[ {}\left (x^{2}+x -2\right ) y^{\prime }+3 \left (1+x \right ) y = x -1 \]

13322

\[ {}x y^{\prime }+x y+y-1 = 0 \]

13323

\[ {}y+\left (x y^{2}+x -y\right ) y^{\prime } = 0 \]

13324

\[ {}r^{\prime }+r \tan \left (t \right ) = \cos \left (t \right ) \]

13325

\[ {}\cos \left (t \right ) r^{\prime }+r \sin \left (t \right )-\cos \left (t \right )^{4} = 0 \]

13326

\[ {}\cos \left (x \right )^{2}-y \cos \left (x \right )-\left (\sin \left (x \right )+1\right ) y^{\prime } = 0 \]

13327

\[ {}y \sin \left (2 x \right )-\cos \left (x \right )+\left (1+\sin \left (x \right )^{2}\right ) y^{\prime } = 0 \]

13328

\[ {}y^{\prime }-\frac {y}{x} = -\frac {y^{2}}{x} \]

13329

\[ {}x y^{\prime }+y = -2 x^{6} y^{4} \]

13330

\[ {}y^{\prime }+\left (4 y-\frac {8}{y^{3}}\right ) x = 0 \]

13331

\[ {}x^{\prime }+\frac {\left (t +1\right ) x}{2 t} = \frac {t +1}{t x} \]

13332

\[ {}x y^{\prime }-2 y = 2 x^{4} \]

13333

\[ {}y^{\prime }+3 x^{2} y = x^{2} \]

13334

\[ {}{\mathrm e}^{x} \left (y-3 \left (1+{\mathrm e}^{x}\right )^{2}\right )+\left (1+{\mathrm e}^{x}\right ) y^{\prime } = 0 \]

13335

\[ {}2 x \left (1+y\right )-\left (x^{2}+1\right ) y^{\prime } = 0 \]

13336

\[ {}r^{\prime }+r \tan \left (t \right ) = \cos \left (t \right )^{2} \]

13337

\[ {}x^{\prime }-x = \sin \left (2 t \right ) \]

13338

\[ {}y^{\prime }+\frac {y}{2 x} = \frac {x}{y^{3}} \]

13339

\[ {}x y^{\prime }+y = \left (x y\right )^{{3}/{2}} \]

13340

\[ {}y^{\prime }+y = \left \{\begin {array}{cc} 2 & 0\le x <1 \\ 0 & 1\le x \end {array}\right . \]

13341

\[ {}y^{\prime }+y = \left \{\begin {array}{cc} 5 & 0\le x <10 \\ 1 & 10\le x \end {array}\right . \]

13342

\[ {}y^{\prime }+y = \left \{\begin {array}{cc} {\mathrm e}^{-x} & 0\le x <2 \\ {\mathrm e}^{-2} & 2\le x \end {array}\right . \]

13343

\[ {}\left (x +2\right ) y^{\prime }+y = \left \{\begin {array}{cc} 2 x & 0\le x <2 \\ 4 & 2\le x \end {array}\right . \]

13344

\[ {}a y^{\prime }+b y = k \,{\mathrm e}^{-\lambda x} \]

13345

\[ {}y^{\prime }+y = 2 \sin \left (x \right )+5 \sin \left (2 x \right ) \]

13346

\[ {}\cos \left (y\right ) y^{\prime }+\frac {\sin \left (y\right )}{x} = 1 \]

13347

\[ {}\left (1+y\right ) y^{\prime }+x \left (2 y+y^{2}\right ) = x \]

13348

\[ {}y^{\prime } = \left (1-x \right ) y^{2}+\left (2 x -1\right ) y-x \]

13349

\[ {}y^{\prime } = -y^{2}+x y+1 \]

13350

\[ {}y^{\prime } = -8 x y^{2}+4 x \left (4 x +1\right ) y-8 x^{3}-4 x^{2}+1 \]

13351

\[ {}6 x^{2} y-\left (x^{3}+1\right ) y^{\prime } = 0 \]

13352

\[ {}\left (3 x^{2} y^{2}-x \right ) y^{\prime }+2 x y^{3}-y = 0 \]

13353

\[ {}y-1+x \left (1+x \right ) y^{\prime } = 0 \]

13354

\[ {}x^{2}-2 y+x y^{\prime } = 0 \]

13355

\[ {}3 x -5 y+\left (x +y\right ) y^{\prime } = 0 \]

13356

\[ {}y^{2} {\mathrm e}^{2 x}+\left (y \,{\mathrm e}^{2 x}-2 y\right ) y^{\prime } = 0 \]

13357

\[ {}8 x^{3} y-12 x^{3}+\left (x^{4}+1\right ) y^{\prime } = 0 \]

13358

\[ {}2 x^{2}+x y+y^{2}+2 x^{2} y^{\prime } = 0 \]

13359

\[ {}y^{\prime } = \frac {4 y^{2} x^{3}-3 x^{2} y}{x^{3}-2 x^{4} y} \]

13360

\[ {}\left (1+x \right ) y^{\prime }+x y = {\mathrm e}^{-x} \]

13361

\[ {}y^{\prime } = \frac {2 x -7 y}{3 y-8 x} \]

13362

\[ {}x^{2} y^{\prime }+x y = x y^{3} \]

13363

\[ {}\left (x^{3}+1\right ) y^{\prime }+6 x^{2} y = 6 x^{2} \]

13364

\[ {}y^{\prime } = \frac {2 x^{2}+y^{2}}{2 x y-x^{2}} \]

13365

\[ {}x^{2}+y^{2}-2 x y y^{\prime } = 0 \]

13366

\[ {}8+2 y^{2}+\left (-x^{2}+1\right ) y y^{\prime } = 0 \]

13367

\[ {}y^{2} {\mathrm e}^{2 x}-2 x +{\mathrm e}^{2 x} y y^{\prime } = 0 \]

13368

\[ {}3 x^{2}+2 x y^{2}+\left (2 x^{2} y+6 y^{2}\right ) y^{\prime } = 0 \]

13369

\[ {}4 x y y^{\prime } = 1+y^{2} \]

13370

\[ {}y^{\prime } = \frac {2 x +7 y}{2 x -2 y} \]

13371

\[ {}y^{\prime } = \frac {x y}{x^{2}+1} \]

13372

\[ {}y^{\prime }+y = \left \{\begin {array}{cc} 1 & 0\le x <2 \\ 0 & 0<x \end {array}\right . \]

13373

\[ {}\left (x +2\right ) y^{\prime }+y = \left \{\begin {array}{cc} 2 x & 0\le x \le 2 \\ 4 & 2<x \end {array}\right . \]

13374

\[ {}x^{2} y^{\prime }+x y = \frac {y^{3}}{x} \]

13375

\[ {}5 x y+4 y^{2}+1+\left (2 x y+x^{2}\right ) y^{\prime } = 0 \]

13376

\[ {}2 x +\tan \left (y\right )+\left (x -x^{2} \tan \left (y\right )\right ) y^{\prime } = 0 \]

13377

\[ {}y^{2} \left (1+x \right )+y+\left (2 x y+1\right ) y^{\prime } = 0 \]

13378

\[ {}2 x y^{2}+y+\left (2 y^{3}-x \right ) y^{\prime } = 0 \]

13379

\[ {}4 x y^{2}+6 y+\left (5 x^{2} y+8 x \right ) y^{\prime } = 0 \]

13380

\[ {}8 x^{2} y^{3}-2 y^{4}+\left (5 y^{2} x^{3}-8 x y^{3}\right ) y^{\prime } = 0 \]

13381

\[ {}5 x +2 y+1+\left (2 x +y+1\right ) y^{\prime } = 0 \]